Knowledge of Gastritis and Dietary Patterns Among Female Senior High School Students - Febiola, Dita; Arif Murtadho, Maulana; Ispriantari, Aloysia (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Gastritis is an inflammation of the gastric mucosa that frequently occurs among female adolescents due to unhealthy dietary patterns such as irregular eating schedules, frequent consumption of irritating foods, and low awareness about digestive health. Knowledge plays an important role in shaping eating behaviors, yet many adolescents tend to underestimate the risk factors of gastritis. This study aimed to determine the relationship between gastritis knowledge and dietary patterns among female senior high school students. Methods: This study used a correlational research design with a cross-sectional approach. The study population was all 116 eleventh-grade female students of Public Vocational High School Malang City, and was selected using total sampling. Data collection used a knowledge questionnaire and a dietary questionnaire. Data were analyzed using the Chi-Square test. Results: The results showed that most respondents had adequate knowledge (61.2%), while 14.7% had good knowledge and 24.1% had poor knowledge. Most respondents (41.4%) had poor dietary habits. Statistical tests showed a p-value of 0.001, indicating a significant relationship between knowledge levels about gastritis and dietary habits. Conclusions: Nurses should design intervention to improve gastritis knowledge to help promote healthier eating behaviors to prevent gastritis.